Respuesta :
Answer:
The answer to your question is x₁ = -3 + [tex]\frac{\sqrt{2}}{2}[/tex] ; x₂ = -3 [tex]- \frac{\sqrt{2}}{2}[/tex]
Step-by-step explanation:
Data
2x² + 12x = -17
Process
1.- Equal to zero
2x² + 12x + 17 = 0
2.- Identify a, b and c
a = 2
b = 12
c = 17
3.- Substitute in the general formula
x = [tex]\frac{-12 +- \sqrt{12^{2} -4(2)(17)}}{2(2)}[/tex]
4.- Simplify
x = [tex]\frac{-12 +- \sqrt{144 - 136}}{4}[/tex]
x = [tex]\frac{-12 +- \sqrt{8}}{4}[/tex]
x = [tex]\frac{-12 +-2 \sqrt{2}}{4}[/tex]
5.- Find x1 and x2
x₁ = -3 + [tex]\frac{\sqrt{2}}{2}[/tex] x₂ = -3 [tex]- \frac{\sqrt{2}}{2}[/tex]
Answer:
Step-by-step explanation:
The given quadratic equation is expressed as
2x² + 12x = - 17
Rearranging the equation so that it will be in the standard form of ax² + bx + c, it becomes
2x² + 12x + 17 = 0
The general formula for solving quadratic equations is expressed as
x = [- b ± √(b² - 4ac)]/2a
From the equation given,
a = 2
b = 12
c = 17
Therefore,
x = [- 12 ± √(12² - 4 × 2 × 17)]/2 × 1
x = [- 12 ± √(144- 136)]/2
x = [- 12 ± √8]/2
x = (- 12 + 2.83)/2 or x = (- 12 - 2.83)/2
x = 4.5 or x = 7.415